2022
DOI: 10.3390/rs14040982
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Assessment of SMAP Level 3 and Level 4 Soil Moisture Products over the Soil Moisture Network within the ShanDian River (SMN-SDR) Basin, China

Abstract: The Soil Moisture Active Passive (SMAP) mission with high-precision soil moisture (SM) retrieval products provides global daily composites of SM at 3, 9, and 36 km earth grids measured by L-band active and passive microwave sensors. The capability of passive microwave remote sensing has been recognized for the estimation of SM variations. The purpose of this work was to establish an interaction between the highly variable SM spatial distribution on the ground and the SMAP’s coarse resolution radiometer-based S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…This outcome indicates that the evaluation accuracy of the SPL3SMP_E soil moisture product aligns closely with its intended design accuracy. This finding is consistent with conclusions drawn from research conducted in other regions [49][50][51]. Simultaneously, the consistently negative values of MD may indicate a prevalent underestimation of soil moisture by the SPL3SMP_E soil moisture product in this specific region.…”
Section: Overall Accuracy Of the Spl3smp_e Soil Moisture Productsupporting
confidence: 91%
“…This outcome indicates that the evaluation accuracy of the SPL3SMP_E soil moisture product aligns closely with its intended design accuracy. This finding is consistent with conclusions drawn from research conducted in other regions [49][50][51]. Simultaneously, the consistently negative values of MD may indicate a prevalent underestimation of soil moisture by the SPL3SMP_E soil moisture product in this specific region.…”
Section: Overall Accuracy Of the Spl3smp_e Soil Moisture Productsupporting
confidence: 91%
“…The downscaled SMAP SM was qualitatively evaluated with the SMN-SDR network at two spatial scales: core validation sites (CVSs), which provide all of the S-scale (S) and a sparse network of M-scale (M) and L-scale (L) stations. In this study, these networks were utilized to compare the SMAP SM downscaled by RF and ANN at 1 km spatial resolution with in situ SM, using a series of statistical metrics, including the ubRMSE [73,74], correlation coefficient (R), and mean Bias [65]. The validating metrics are defined as follows:…”
Section: Discussionmentioning
confidence: 99%
“…The near-SSM (0-5 cm) is determined by using radiometric-based methods with a volumetric accuracy of 0.04 m 3 /m 3 [63]. As a result, SMAP's passive SM product is crucial for examining and analyzing in SM conditions throughout the world, and recent validation experiments have shown that it has a strong potential to accurately capture SSM dynamics [13,64,65].…”
Section: Data 221 Smap Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It employed both an L-band radar and an L-band radiometer, and the latter was identified as the best choice to retrieve SM [73]. Compared with other satellite-based SM data, the SMAP Level 3 products perform best on grassland in arid and semi-arid areas [74][75][76][77]. Thus, we selected the SMAP Level 3 daily scale products with a resolution of 9 km in the growth seasons of 2017-2019 at the DGS and of 2020 at the AGS.…”
Section: The Soil Moisture Active and Passive Missionmentioning
confidence: 99%